Transformation of organic nitrogen fractions with different molecular weights during different organic wastes composting. (August 2018) - Zhou, Haixuan; Zhao, Yue; Yang, Hongyu; Zhu, Longji; Cai, Baiyan; Luo, Sheng; Cao, Jinxiang; Wei, Zimin
Graphical abstract: Highlights: The mechanism of N transformation during composting of CM is HMW ON → LMW ON → NH4 + . The mechanism of N transformation during composting of GW and MSW is HMW ON → LMW ON. Bacterial community is the main driver of the N mineralization during CM composting. Abstract: This study aimed to investigate different transformation mechanisms of organic nitrogen (N) fractions during composting with different raw materials, and the contributions of bacterial communities and environmental factors to organic N fractions transformation. The results showed that high molecular weight organic N was first degraded to low molecular weight organic N and then turned into NH4 + during chicken manure composting. In comparison, organic N fractions were stored in composts rather than mineralization during garden waste and municipal solid waste composting. Meanwhile, bacterial communities, environmental factors and the combination of them were the main drivers of N transformation during chicken manure, municipal solid waste and garden waste composting, respectively. In conclusion, the proposed organic N transformation mechanisms in this study provided a theoretical basis for improving the quality of compost products.